Investigation Study of Effectiveness Solar Renewable Energy Installation at on Site Installation - Zeckrey Jikurun; Ahmad Mukifza Harun; Shahril Yusof (2018)
This paper presents the installation study of solar renewable energy at UMS peak. The single line diagram for the renewable energy study will be design and explain thoroughly in this paper, the design will be based on off grid system photovoltaic. The expected solar power generation will be calculated and the efficiency of the system will be discussed. The efficiency of energy storage capacity also will be discussed in this paper.